Improving Accounting Students' Statistical Understanding of 2-Way ANOVA Through a Case Study of Indonesian Coffee Exports - Nicholas Renaldo; Suhardjo; Andi; Tandy Sevendy; Intan Purnama (Reflection: Education and Pedagogical Insights, 2023)
The phenomenon that exists in this study is the lack of understanding of accounting students in understanding analysis of variance or better known as ANOVA, especially 2-way ANOVA. This study uses the case of Indonesian coffee exports. This research in its early stages will explain the 2-way ANOVA analysis according to the data presented. Then in the second stage will explain students' understanding of the 2-way ANOVA method. The level of understanding of accounting students regarding the 2-Way ANOVA method is still low. This is caused by factors of education level, curriculum, and experience. Significant 2-way ANOVA test results can open up opportunities for in-depth follow-up research. For example, a more detailed analysis of the significant factors and exploration of more complex interactions between the variables involved can be carried out.